The use of monoclonal antibodies to demonstrate antigenic variation between influenza A (H1N1) isolates from Johannesburg - Martin, Desmond. James. (My University, 1991)
Since the reappearance of the influenza A( H, N, ) subtype in 1977, the virus has shown progressive antigenic variation in isolates from other parts of the world. The virus showed more rapid evolution in the latter part of the 1980 decade. To determine if this variation of the virus was present in local influenza outbreaks, sequential isolates from the 1989 influenza season were studied. The 1989 season saw increased activity of both the HjN! and H3N2 subtypes. The majority of the HjNj isolates were from subjects bom after 1957. A panel
A dissertation submitted to the Faculty of Medicine, University of the Witwatersrand, in partial fulfilment of the requirements for the degree Master of Medicine (Virology)
Keywords: Influenza A Virus; H1N1 Subtype; Antibodies, Monoclonal